A comparative study on self-medication practice of analgesics among MBBS students of Dr. B. R. Ambedkar Medical College, Bengaluru - M., Poorvi; R., Veena D.; H., Shwetha; P., Shanmukananda (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Self-medication with analgesics is prevalent worldwide among medical students due to easy availability of drugs and may lead to irrational usage of drugs. To assess knowledge, attitude, practice and perception of self-medication of analgesics. Methods: A comparative study on self-medication of analgesics was conducted on 3rd and 5th term Bachelor of medicine and Bachelor of Surgery (MBBS) students of Dr. B. R. Ambedkar Medical College, Bengaluru in November 2019. A pre-designed questionnaire was used to collect information on self-medication with analgesics. Results: 74.5% of 3rd term and 65.5% of 5th term MBBS students practiced self-medication with analgesics. Majority of students in both groups had some knowledge on self-medication with analgesics. Common condition for using analgesic self-medication was headache (75.8%, 59.7%, p=0.0172) and non-steroidal anti-inflammatory drugs (80.6%, 90%, p=0.0780) were commonly used analgesics. Analgesics were used for quick relief (67.7%, 73.3%, p=0.4512) and students in group II referred medical textbooks as a source of information for practicing self-medication with analgesics (22.5%, 61.6%, p<0.001). Students agreed that self-medication is acceptable for medical students (45.8%, 43%, p=0.045) and medical license is required for better administration of drugs (51.3%, 63.2%, p=0.225). Conclusions: This study has found that self-medication with analgesics was common among MBBS students for minor illness. It is necessary to create awareness and educate students regarding the hazards of self-medication.